Educational Leadership Emotional Based Spiritual Quotient (ESQ) Model Ary Ginanjar Agustian - Mukhasin, Mukhasin (Al-Ilmu, 2025)
This study discusses educational leadership based on the Emotional Spiritual Quotient (ESQ) Model of Ary Ginanjar Agustian. The methodology used in this study is qualitative research with the type of library research and using a content analysis approach. The data in this study were collected using documentation techniques. From the results of the research conducted, it can be concluded that the ESQ model concept initiated by Ary Ginanjar can be used as a basis for educational leadership because it encourages harmony between intellectual, emotional, and spiritual intelligence into a single unity of tauhid, even starting from the level of mindset to the stage of implementing attitudes and behaviors shown by a person. This can be seen especially from the six principles initiated by Ary Ginanjar which include the star principle, angel principle, leadership principle, learning principle, vision principle, well organized principle. These principles contain the main ideas in building and instilling intellectual, emotional and spiritual intelligence at the same time which are very much needed and relevant to the concept of leadership in educational institutions